The concept "international arbitration" in the context of professional training of future arbitration lawyers - Оlga Nagorna (Vasyl Stefanyk Precarpathian National University, 2017)
International arbitration is an effective alternative mechanism for dispute resolution between the parties to the treaty in the context of globalization. Nowadays there is a demand for optimal organization of education and training specialists, capable to realize arbitration practice in the international arena. Professional training of future arbitration lawyers is carried out within master programs. In addition to professional disciplines, the curriculum includes the study of Business English as a component of professional competence of future arbitration lawyers and a tool for their professional interaction. To create reliable conditions for high-quality foreign language training, a lecturer has to obtain certain another sphere knowledge, in particular to understand the essence of the concept "international arbitration". Key words: international arbitration, professional training, future arbitration lawyer, master program, Business English